Pendekatan Pemecahan Desain Interior Rumah Tinggal - Sunarmi Sunarmi (Ornamen, 2013)
This paper is a review of literature that discusses the resultsof " Solving Approach Interior Design House Live " is a residentialinterior container as a private place for people to shelter thatcan reveal or reflect the attitudes and personal life as well aswell as a place residents formed human personality . Personalitycan be defined as an attitude or human responses to the eventsaround him . The function is to meet the physical and psychologicalneeds of human existence as a form of individual and social. Level needs of the residents affected by lifestyle or profession ,desires , hobbies , gender , age , economic . Interior design elementscomprising : Activities , Needs Space and Layout Spaces, Elements Shaping Space , Space Filling / Furniture , Conditioning, and Lay Out . Residential interior design approach include :Human Behavior , Lifestyle Market Orientation , and , PhilosophyShape . Approach to human behavior is is planning to make thebehavior as a factor to be considered in planning related to thesubject of interior design to formulate jenir space and form elements. Lifestyle approach is to make the planning profession asa basis for formulating the type and shape of the container interiorelements for professional development activities . Interior designis more concentrated on determining the type of space and shapespace as a place of everyday life and professional development. Solving approach to a market-oriented design is the planningthat led to the completion of design and attention to general usersgrouped by gender , age , class / economic group , class socialclass / status to determine the shape of the interior . Approachis a form of planning design philosophy that makes philosophya form of expressing the meaning behind a real visualized form .Keywords : Interior , approach , residence , lifestyle